Gegar Budaya Terhadap Model Komunikasi Lintas Budaya Mahasiswa Pada Program International Credit Transfer di Filipina - Azizah Pratiwi; Mentari Sukma Yanti; Ayu Arnita; Ami Asnaini; Sitti Indah Mardia; Tri Indah Rusli (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
Visiting foreign countries, individuals often encounter cultural shock,and this holds true for students participating in the International Credit Transfer program while pursuing their studies in the Philippines. Effective adaptation and communication are essential in navigating these cultural challenges. This research aims to explore the impact of culture shock on cross-cultural communication among students attending lectures in the Philippines. Qualitative research methods, including fenomenology approaches,observation, and interviews, were employed to collect data. The participant selection method utilized purposive sampling. Data from observations and interviews were analyzed using thematic analysis. The findings reveal that students engaged in exchange programs in the Philippines experience culture shock. This research classifies the causes of culture shock among exchange students in the Philippines into internal and external factors. Furthermore, the study demonstrates that successful adaptation to culture shock occurs during the final stage, as evidenced by cultural adaptation actions taken by students participating in the International Credit Transfer program in the Philippines.